DEMOKRASI YANG BERAKAR : PENDIDIKAN KEWARGANEGARAAN SEBAGAI MEDIA INTERNALISASI NILAI DEMOKRATIS - Tarom, Muhammad (LPPM UNSAP & FISIP UNSAP, 2025)
The era of reform and democracy is currently sweeping through social, national, and state life. However, the format for democratic maturity or a truly democratic society has yet to be realized. Attitudes and behaviors that deviate from the norms of a democratic society still often emerge. To achieve a democratic society, various efforts are required, including the implementation of citizenship education. The aim of citizenship education is to form democratic, civilized, intelligent, and responsible citizens for the sustainability of their nation and state. The success of democracy is reflected in how far democratic principles are practiced and mutually agreed upon by citizens and the state. Becoming democratic requires norms that serve as a reference for a democratic social order. These norms include awareness of pluralism, deliberation, freedom of conscience, equality of rights and obligations, and honesty in decision-making processes